Paloma wants to be Lady Freedom - Campos-Duffy, Rachel (Regnery Kids, 2019)
"While lost inside the magnificent building, Paloma becomes enchanted with the statue of Lady Freedom, learns about her immigrant father's dreams, and discovers her own courage and love for America." --Amazon.